Impacto de la pandemia en la empresa Transpecarba S.A.: aplicación de indicadores de liquidez, endeudamiento y rentabilidad. - Mendieta Castro, Tiffany Michelle; Saltos Apolo, Carla Marena (My University, 2021)
The appearance of Covid-19 has sharply damaged the world economy. In Ecuador, the restriction measures ordered by the pandemic greatly affected the economy of the country's companies. Due to the current changes in the business environment with respect to the pandemic, most of the companies have incurred economic and financial problems, the worst case being the closure of their activities; It is then where the financial indicators intervene that would facilitate the obtaining of more accurate information regarding the business situation. The research aims to analyze the economic and financial impact of the company Transpecarba S.A. through the financial indicators of liquidity, indebtedness and profitability, determining the situation of the entity in times of Covid-19. For this, a descriptive methodology with a qualitative approach has been used, using the figures given by the financial statements to perform the respective indicators, in addition to the interview that allowed us to have privileged information about the company. The results obtained according to each group of indicators made it possible to demonstrate the reality of each ratio, and by analyzing each of them it was possible to determine a favorable and unfavorable economic impact on the parameters studied
La aparición del Covid-19 ha perjudicado bruscamente la economía mundial. En el Ecuador, las medidas de restricción dispuestas por la pandemia, afectaron en gran magnitud a la economía de las empresas del país. Debido a los cambios presentes en el medio empresarial respecto a la pandemia, la mayoría de las empresas, han incurrido en problemas económicos y financieros, siendo el peor de los casos el cierre de sus actividades; es entonces donde intervienen los indicadores financieros que facilitarían la obtención de información más acertada respecto a la situación del negocio. La investigación tiene como objetivo analizar el impacto económico y financiero de la empresa Transpecarba S.A. a través de los indicadores financieros de liquidez, endeudamiento y rentabilidad, determinando la situación de la entidad en tiempos de Covid-19. Para ello se ha empleado una metodología descriptiva con enfoque cualitativo, utilizando las cifras dadas por los estados financieros para realizar los respectivos indicadores, además de la entrevista que nos permitió tener información privilegiada de la situación del negocio. Los resultados obtenidos según cada grupo de indicadores permitió evidenciar la realidad de cada ratio, y analizando cada uno de ellos se consiguió determinar un impacto económico favorable y desfavorable en los parámetros estudiados.
Keywords: PANDEMIA; COVID-19; RATIOS FINANCIEROS; TRANSPORTE DE CARGA PESADA